2022
DOI: 10.1177/00110000211070597
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Racism, Internalized Racism, and Psychological Outcomes Among East Asians/East Asian Americans

Abstract: The present study investigated the psychological effects of racism on East Asians and East Asian Americans (EAEAAs) living in the United States during the COVID-19 pandemic using a mixed-methods approach. First, using an autoregressive cross-lagged panel analysis, we investigated the relations between COVID-19 racism, internalized racism, psychological distress, and social isolation among EAEAAs. We then examined the impact of the COVID-19 pandemic on EAEAAs using consensual qualitative research-modified. Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…As recommended by the scale developers (Choi et al, 2017), a total score of all items was used to measure internalized racism in this study, with higher mean scores indicating greater internalized racism (Choi et al, 2017). Prior research of the scale demonstrated an estimate of .88–.92 (Ahn et al, 2022). The internal consistency estimate for the present study was similar ( a = .88).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As recommended by the scale developers (Choi et al, 2017), a total score of all items was used to measure internalized racism in this study, with higher mean scores indicating greater internalized racism (Choi et al, 2017). Prior research of the scale demonstrated an estimate of .88–.92 (Ahn et al, 2022). The internal consistency estimate for the present study was similar ( a = .88).…”
Section: Methodsmentioning
confidence: 99%
“…Internalized racism stems from both covert and overt forms of racism (K. Pyke & Dang, 2003). While there is variability in how individuals are affected by racial discrimination, it is plausible that the deep-seated and more recent COVID-19-related racism may trigger Asian Americans to accept oppression and negative stereotypes as a means of survival (Ahn et al, 2022). This may lead to the internalization of bias and oppression toward one's group, creating conflict between Asian Americans' heritage, people, families, and communities (Hwang, 2021).…”
Section: Internalized Racismmentioning
confidence: 99%
“…A recent Pew Research Center report found that approximately 31% of Asian American adults reported being the subject of slurs or jokes because of their race or ethnicity, and about 58% of Asian American adults shared that it is more common for people to express racist or racially insensitive views about Asians than it was before the COVID-19 outbreak (Ruiz et al, 2020). Additional reports have also found high rates of anti-Asian racist and violent acts (e.g., physical assault, verbal harassment, online racial discrimination, property damage and vandalism; Tessler et al, 2020); these were believed to be results of anti-Asian discrimination (Ahn et al, 2022; Borja et al, 2020; Cheah et al, 2020). There is an urgent need to better understand how these experiences of racial discrimination impacted Asian American parents during this particularly stressful time, as well as how well-researched psychological processes, such as emotion regulation, may act as a risk or protective factor in these experiences.…”
Section: Racial Discrimination and Covid-19 Discrimination Fearmentioning
confidence: 99%
“…Despite its novelty as one of the first quantitative explorations of queer Asian American men's dating preferences, the current study nonetheless possessed many limitations. First, because we collected our data from November 2020 to January 2021; it is also possible that witnessing and experiencing the COVID-19 pandemic instilled within participants a heightened awareness of anti-Asian racism (Ahn et al, 2022), compared to queer Asian American men in prior research. The survey administered to assess the present study's variables of interest could also be improved for future studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%